2016
DOI: 10.1123/ijatt.2014-0143
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Bracing Decreases Vertical Jump Height and Alters Lower Extremity Kinematics

Abstract: The purpose of this study was to determine the effects of ankle bracing on vertical jump performance and lower extremity kinematics and electromyography (EMG) activity. Twenty healthy college athletes participated in two sessions, separated by a minimum of 24 hr. They performed five jumps with no brace on the first day, and five jumps with both ankles braced on the second day. An average of the three highest jumps each day was used for analysis. Braced vertical jump performance significantly decreased (p = .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…37 Studies have shown that the taped ankle diminished muscle activity and the rate of inversion on the ankle. 17,18,38 This is also demonstrated by wearing an ankle brace, restricting dorsiflexion and plantarflexion 39,40 as compared when there is no tape applied after ground contact during drop landing for LG. 32 Due to the restriction brought about by the tape at the ankle joint, the eccentric action of the gastrocnemius is limited, therefore less energy is absorbed to control the movement, 38 and there is a decreased need to provide mechanical stability.…”
Section: Discussionmentioning
confidence: 95%
“…37 Studies have shown that the taped ankle diminished muscle activity and the rate of inversion on the ankle. 17,18,38 This is also demonstrated by wearing an ankle brace, restricting dorsiflexion and plantarflexion 39,40 as compared when there is no tape applied after ground contact during drop landing for LG. 32 Due to the restriction brought about by the tape at the ankle joint, the eccentric action of the gastrocnemius is limited, therefore less energy is absorbed to control the movement, 38 and there is a decreased need to provide mechanical stability.…”
Section: Discussionmentioning
confidence: 95%
“…Ankle orthoses are biomechanically designed using a wide variety of materials to control, limit, and immobilize the motion for ankle joint. This effect of jump performance may be due to a decrease in the ankle range of motion (ROM) in the sagittal plane [ 10 , 11 ], rectus femoris and calf muscle activity [ 8 , 9 , 11 ], or vertical ground reaction force (VGRF) [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, ankle orthotics may have a negative impact on athlete performance in activities such as sprinting [2], cutting [3], jump landing [4,5], and vertical jumping [2]. Furthermore, there is a consensus that ankle orthotics reduces the vertical jump height [6][7][8][9][10][11][12]. This may be due to a decrease in the ankle range of motion (ROM) in the sagittal plane [10,11], rectus femoris and calf muscle activity [8, 9,11], or vertical ground reaction force (VGRF) [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a consensus that ankle orthotics reduces the vertical jump height [6][7][8][9][10][11][12]. This may be due to a decrease in the ankle range of motion (ROM) in the sagittal plane [10,11], rectus femoris and calf muscle activity [8, 9,11], or vertical ground reaction force (VGRF) [8,12]. However, since the ankle orthosis-related decrease in jump height is small (0.013 m), it is controversial whether ankle orthotics in uences vertical jump performance during practice or competition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation